Re-live the River: Regenerating decaying blue ecosystems through Architecture - Wrennö, Henrik (My University, 2020)
Relive the River is a Thesis that investigates the potential of regenerating a severely modified natural water flow through architecture. The aim with the report is to develop appropriate architectural methods to create multi-specie coexistence by the urban riverbank. The project will elaborate on possibilities to regenerate decaying aquatic eco-systems through design and find out how these interventions can benefit the Gothenburg region. The project will analyze the most suitable locations in the urban periphery to intervene by using landscape and architecture as tools to find configurations best suited for the purpose. The central program of the development will include habitat, recreation and education, serving every specie enjoying the aquatic and riparian zone. As catalyzing ecosystems has many bounded benefits the project will further investigate the potential of simultaneously working as a water rehabilitation provider, serving Göta Älv River and its tethered bio-diversity with natural water purification.